Drivers of Sustainable Entrepreneurship Among SMEs in Pakistan: Does Entrepreneurial Knowledge Matter? - Abdul Hanan; Anis Shahira; Mohsin Ali (CV. Literasi Indonesia, 2021)
Developing the concept of sustainable entrepreneurship from upper echelons theory and resource-based view theory, this research explores the impact of sustainable entrepreneurship among small and medium-sized enterprises. Sustainable entrepreneurship pursues a motivating approach to the economic, social, and environmental objectives of the society. The purpose of the study is to delve into the influencing factors of sustainable entrepreneurship among SMEs. The research is based on a quantitative approach via survey to address the sustainable entrepreneurship among SMEs (e.g., Punjab) in Pakistan. Data were obtained from 330 employees working in manufacturing SME’s. Additionally, structural equation modelling (SEM) was tested to examining the hypothesized relationship. The results confirm a positive effect of sustainability orientation and entrepreneurial orientation on sustainable entrepreneurship and the moderating effect of entrepreneurial knowledge was found significant. Moreover, the results confirm a negative effect of entrepreneurial bricolage on sustainable entrepreneurship, and the moderating effect of the entrepreneurial knowledge was found to be insignificant. However, these researches carry-out the context of entrepreneurial bricolage acts as a moderator in sustainable entrepreneurship research. Based on the findings, this research provides implications for the policymakers to promote sustainable entrepreneurship to facilitate new markets and getting the foremost advantage of sustainable development in SME’s.